2006
DOI: 10.1063/1.2206973
|View full text |Cite
|
Sign up to set email alerts
|

Correlating ion energies and CF2 surface production during fluorocarbon plasma processing of silicon

Abstract: Ion energy distribution ͑IED͒ measurements are reported for ions in the plasma molecular beam source of the imaging of radicals interacting with surfaces ͑IRIS͒ apparatus. The IEDs and relative intensities of nascent ions in C 3 F 8 and C 4 F 8 plasma molecular beams were measured using a Hiden PSM003 mass spectrometer mounted on the IRIS main chamber. The IEDs are complex and multimodal, with mean ion energies ranging from 29 to 92 eV. Integrated IEDs provided relative ion intensities as a function of applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(24 reference statements)
2
11
0
Order By: Relevance
“…4 It is known from spatially resolved laser‐induced fluorescence (LIF) measurements on growing fluorocarbon films that CF 2 radicals are generated at the substrate surface through plasma interactions with the growing film 26. Recently, it was shown that the CF 2 surface production is linearly correlated to the mean ion energies within the fluorocarbon discharges 27. Therefore, the concept of chemical quasi‐equilibrium might not be applicable in this case, since the plasma polymerization might be strongly influenced by energetic particles (no radical‐dominated process), and the substrate surface cannot be considered as passive zone.…”
Section: Resultsmentioning
confidence: 99%
“…4 It is known from spatially resolved laser‐induced fluorescence (LIF) measurements on growing fluorocarbon films that CF 2 radicals are generated at the substrate surface through plasma interactions with the growing film 26. Recently, it was shown that the CF 2 surface production is linearly correlated to the mean ion energies within the fluorocarbon discharges 27. Therefore, the concept of chemical quasi‐equilibrium might not be applicable in this case, since the plasma polymerization might be strongly influenced by energetic particles (no radical‐dominated process), and the substrate surface cannot be considered as passive zone.…”
Section: Resultsmentioning
confidence: 99%
“…It is known from spatially resolved laser-induced fluorescence (LIF) measurements on growing fluorocarbon films that CF 2 radicals are generated at the substrate surface through plasma interactions with the growing film [25]. Recently it was shown that the CF 2 surface production is linearly correlated to the mean ion energies within the fluorocarbon discharges [26]. Therefore, the concept of chemical quasi-equilibria might not be applicable, since the plasma polymerization might be strongly influenced by energetic particles (no radical-dominated process) and the substrate surface cannot be considered as passive zone.…”
Section: Fluorocarbon Dischargesmentioning
confidence: 99%
“…Average ion energy ⟨ E i ⟩ values in our systems increase significantly with increasing y / x ratio of the precursor, such that the total average ion energies in the CF 4 plasma system are approximately twice those of the C 3 F 6 system. We have previously demonstrated that ion bombardment can be a major contributing factor in surface production of CF 2 , and that ⟨ E i ⟩ and S values correlate linearly. , Thus, ions may be partially responsible for the rise seen in S as the plasma precursor y / x ratio increases. A third contributing factor to consider is the relative distribution of electronically excited CF n states in the plasma gas-phase.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously demonstrated that ion bombardment can be a major contributing factor in surface production of CF 2 , and that ⟨E i ⟩ and S values correlate linearly. 16,33 Thus, ions may be partially responsible for the rise seen in S as the plasma precursor y/x ratio increases. A third contributing factor to consider is the relative distribution of electronically excited CF n states in the plasma gas-phase.…”
Section: ■ Discussionmentioning
confidence: 99%